Effect of different levels of nitrogen and phosphorus on nutrient uptake and quality of soybean [Glycine max (L.) Merrill]: EFFECT OF NITROGEN AND PHOSPHORUS ON NUTRIENT UPTAKE AND QUALITY OF SOYBEAN - RAGHUVEER; J A HOSMATH (Journal of Oilseeds Research, 2018)
A field experiment was conducted to study the effect of different levels of nitrogen and phosphorus on nutrient uptake and quality of soybean during kharif 2015. There were twelve treatment combinations consisted of three levels of nitrogen (20, 40 and 60 kg N/ha) and four levels of phosphorus (40, 60, 80 and 100 kg P2O5/ha). Significantly higher soybean seed yield (25.77 q/ha), haulm yield (31.32 q/ha), uptake of nitrogen (209.16 kg/ha), phosphorus (28.09 kg/ha), potassium (114.47 kg/ha) and protein yield (8.81 q/ha) recorded with combined application of nitrogen @ 60 kg/ha and phosphorus @ 80 kg/ha compared to other treatments and it was on par with application of nitrogen @ 60 kg/ha and phosphorus @ 100 kg/ha. Application of nitrogen @ 60 kg, phosphorus @ 80 kg and potash @ 25 kg per hectare found optimum to obtain substantial soybean seed yield.